Breast Radiation Exposure in Female Orthopaedic Surgeons. (2nd November 2016) - Valone, Lindsey C.; Chambers, Monique; Lattanza, Lisa; James, Michelle A.
Abstract : Background: Breast cancer prevalence is higher among female orthopaedic surgeons compared with U.S. women. The most common breast cancer site, the upper outer quadrant (UOQ), may not be adequately shielded from intraoperative radiation. Factors associated with higher breast radiation exposure (protective apron size and type, surgeon position, and C-arm position) have yet to be established. Methods: An anthropomorphic torso phantom, simulating the female surgeon, was placed adjacent to a standard operating table. Dosimeters were placed over the UOQ and lower inner quadrant (LIQ) of the breast, bilaterally. Scatter radiation dose-equivalent rates were measured during continuous fluoroscopy to a pelvic phantom (simulating the patient). Four apron sizes (small, medium, large, and extra-large), 2 apron types (cross-back and vest), 2 surgeon positions (facing the table and 90° to the table), and 2 C-arm positions (anteroposterior and cross-table lateral projection) were tested. Results: The median dose-equivalent rate of scatter radiation to the UOQ (0.40 mrem/hr) was higher than that to the LIQ of the breast (0.06 mrem/hr) across all testing, although this was not statistically significant (p = 0.05). The cross-back aprons provided higher protection to the LIQ compared with the vests (p < 0.05). Lead protection in sizes that were too small or too large for the torso had higher breast radiation dose-equivalent rates. C-arm cross-table lateral projection was associated with higher breast radiation exposure (0.98 mrem/hr) compared with anteroposterior projection (0.13 mrem/hr) (p < 0.001). Conclusions: Breast radiation exposure is higher in a C-arm lateral projection compared with an anteroposterior projection. Higher dose-equivalent rates were observed for the UOQ compared with the LIQ of the breast and for aprons that were too small or too large, although these differences did not reach significance. Factors that may reduce radiation exposure include lead protection of appropriate size and distancing the axilla from the patient and x-ray tube. Clinical Relevance: Increased breast cancer prevalence has been reported for female orthopaedic surgeons. The UOQ of the breast may be at risk for intraoperative radiation exposure. Methods of reducing exposure are warranted.